2008
DOI: 10.1590/s0101-60832008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de depressão na doença de Parkinson

Abstract: ResumoContexto: O reconhecimento da prevalência da depressão em pacientes com doença de Parkinson (DP) é necessá-rio para o desenvolvimento de práticas direcionadas ao tratamento da depressão e a melhora na qualidade de vida deles. Objetivo: Identificar na literatura indexada estudos relacionados à prevalência de depressão na DP, visto que normalmente há sub-reconhecimento e subdiagnóstico da comorbidade. Métodos: Levantamento de artigos no PubMed, LILACS e SciELO que cumpriram com as palavras-chave: prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
12
0
9
Order By: Relevance
“…27 . Given that the literature 8,9,10,11,12,13 indicates a strong inverse association between quality of life and depression, we expected to find a negative relationship between the variables that explained better perceived quality of life and depressive symptoms in the elderly. The results confirmed the model, since an inverse relation was seen between the variables associated with better perceived quality of life and BDI (social class: r = -0.21, p < 0.001; self-rated health status: r = -0.34, p < 0.001; volunteer work: r = -0.14, p = 0.009; medication: r = -0.19, p < 0.001; data collection setting: r = -0.21, p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…27 . Given that the literature 8,9,10,11,12,13 indicates a strong inverse association between quality of life and depression, we expected to find a negative relationship between the variables that explained better perceived quality of life and depressive symptoms in the elderly. The results confirmed the model, since an inverse relation was seen between the variables associated with better perceived quality of life and BDI (social class: r = -0.21, p < 0.001; self-rated health status: r = -0.34, p < 0.001; volunteer work: r = -0.14, p = 0.009; medication: r = -0.19, p < 0.001; data collection setting: r = -0.21, p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
“…Since quality of life is a multidimensional construct, it is potentially influenced by a wide range of variables, including socio-demographic 3,4,5,6 , psychosocial 3,5,7 , and health-related 3,6,7,8,9,10,11,12,13,14 . For the first group of variables, studies have shown that elders' mean family income and level of schooling are positively associated with quality of life 5 .…”
Section: Os Objetivos Do Estudo Foram: (A) Investigarmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a complex etiology, involving base ganglia and gives rise to movement, muscular and postural disturbances [4], contributing to a marked decline of patients life quality with implications at family, social and fi nance levels.…”
Section: Introductionmentioning
confidence: 99%
“…A DP é considerada a segunda doença neurodegenerativa senil mais comum (Nakabayashi et al, 2008) Quando a doença se encontra em fase mais avançada e não apresenta mais os resultados esperados com o uso dos medicamentos, um recurso que pode ser oferecido é a intervenção cirúrgica, que é indicada baseada na condição clínica e física que o indivíduo encontra-se . Este tipo de intervenção vem sendo aprimorada e aperfeiçoada ao longo dos tempos, com técnicas e abordagens melhoradas, de modo a suprir e melhorar a vida do doente (TERRA et al, 2016).…”
Section: Epidemiologiaunclassified